PERAN KOMUNIKASI ORANG TUA DALAM MEMBANGUN KARAKTER ANAK DI DESA PANONGAN - Nila Amalia Nabila; Shakira Annisa (Triwikrama: Jurnal Ilmu Sosial, 2025)
This study aims that parents have a very important role for educating in shaping children's character. Parents need to learn about how to develop or shape character in their children starting from an early age so that good character can be formed and the character can last until adulthood. This study uses qualitative theoretical and practical to describe in detail the Role of Parental Communication in Building Children's Character in Panongan Village. The study focuses on the influence arising from parental communication in building children's character. The survey result is the formation of a child's character must begin with the role of parents because parents are the first education for their children and children's character is formed because of the role played by parents in the form of positive communication where they are open to each other and not only verbal communication but also the behavior of parents, both positive and negative. Parents must continue to provide good examples so that they will be able to carry out their duties and functions better. In addition, parents will also be able to play themselves as wiser parents in the eyes of their children. Because children's behavior is modeled after their parents.The survey result show that the answer come from interviews we conducted in Panongan village. The results of this study show that parents have an important role in forming children's character and children can imitate the behavior that their parents often do. Therefore, parents must set an example of good behavior for their children from as early an age as possible so that they have good character.